EFFECT OF SUPPLEMENTARY FEEDING OF GOLDEN SNAIL FLOUR (POMACEA ANALICULA) WITH DIFFERENT DOSES OF COMMERCIAL FEED ON MILKFISH (CHANOS CHANOS) AT RANDUSANGA WETAN BREBES REGENCY CENTRAL OF JAVA - Narto Narto; Suyono Suyono; Putri Korinur Angeli (Sean Institute, 2022)
Milkfish (Chanos chanos) are plant eaters such as moss, klekap, and plankton (both vegetable and animal). This fish is also one of the economically important types of fish because it is widely consumed by the people of Southeast Asia, especially in Indonesia. Gold snail is an additional alternative material for animal protein source and can reduce or replace fish meal in feed formulations. This study aimed to determine the effect of adding gold snail flour to commercial feeds on the growth of milkfish fry and the best dose of gold snail flour in culling milkfish. The method used in this study is an experimental method with a completely randomized design (CRD). Consisting of 3 treatments and 1 control with 3 replications. treatment A: 100% golden snail flour, treatment B: 75% commercial feed + 25% gold snail flour, treatment C: 50% commercial feed + 50% gold snail flour, control: 100% commercial feed. The study’s results showed that adding gold snail flour to commercial feed had a very significant effect on absolute individual weight growth, absolute length growth and food conversion ratio and had no significant effect on daily growth rate and relative growth rate. The best treatment was treatment B (75% coercive feed + golden snail flour 25%).